Magnetic beads as intravesical foreign bodies in children: our clinical experience - Zeng, Yefeng; Huang, Shaogang; Yang, Zhilin; Gu, Xianbin; Sun, Xuerui; Chen, Pengyu; Li, Shoulin (Frontiers in Pediatrics, 2025)
PurposeTo analyze the clinical data of five patients involving intravesical magnetic beads, summarizing diagnostic and therapeutic experiences.MethodsFrom January 2018 to November 2023, five pediatric patients were treated for intravesical magnetic beads at Shenzhen Children's Hospital. We retrospectively reviewed and analyzed the records of these patients, including demographic characteristics, clinical symptoms, imaging studies, and treatment methods.ResultsAll intravesical magnetic beads were retrieved from patients’ bladders. The patients ranged from 12 to 14 years, with a mean age of 13 years. None of them had a history of psychiatric disorders. Depending on the number of magnetic beads, their aggregation state, and the time since insertion, Three cases were successfully retrieved via cystoscopy, one via pneumovesicoscopy, and another via open surgery. No complications were observed during the postoperative follow-up.ConclusionMagnetic beads are a relatively rare type of intravesical foreign bodies and should be surgically removed as soon as possible. Cystoscopy is the first method for both diagnosis and treatment. When magnetic beads cannot be retrieved via cystoscopy, pneumovesicoscopy may be a viable option for the retrieval of foreign bodies. When endoscopic techniques are unsuitable or have failed, open surgery is a necessary option.